Primary Adrenal Malignancies - Tiberio, Guido A. M.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
Dissemination of knowledge is the best and only strategy capable of improving clinical management in rare and ultra-rare malignancies, including primary adrenal malignancies. It is preliminary to any further healthcare policy such as, for example, the centralization of cases in referral institutions. Adrenal primary malignancies are probably the rarest among rare pathologies. This epidemiological consideration is at the origin of a vicious circle: the lack of preoperative diagnosis leads to inappropriate surgical procedures and to inadequate follow-up and systemic therapy strategies. Furthermore, when malignancy is recognized, the relative role of systemic, surgical, or other local ablative techniques is often misinterpreted. All this produces a negative impact on survival, also in patients who could have been cured with a correct therapeutic strategy. This open access book provides a user-friendly exploration of these rare conditions, using a transversal approach common in modern precision medicine. The text covers various clinical aspects, including epidemiology, genetics, molecular medicine, imaging, and surgery. Guidelines for managing syndromic situations are provided. The book thoroughly addresses all the different surgical issues and emphasizes the importance of pathology in assessing prognosis. The pivotal role of medical oncologists in managing these patients is explored, along with alternative treatments such as nuclear medicine and radiotherapy. Finally, the book highlights the latest preclinical research and its implications for translational medicine.
1. Epidemiology, Presentation, Staging, and Prognostic Factors in Adrenocortical Carcinoma -- 2. Epidemiology, Presentation, Staging, and Prognostic Factors in Malignant Pheochromocytoma -- 3. Genetics and Molecular Biology of Adrenocortical Carcinoma -- 4. Genetics and Molecular Biology of Pheochromocytoma and Paraganglioma -- 5. Imaging in Adrenocortical Carcinoma and Malignant Pheochromocytoma -- 6. Management of Endocrine Syndromes Associated with Adrenocortical Carcinoma -- 7. Management of Hereditary Syndromes Associated with Pheochromocytoma/Paraganglioma -- 8. Adrenal Incidentaloma -- 9. Surgery for Adrenocortical Carcinoma -- 10. Adrenocortical Carcinoma with Vena Cava Involvement -- 11. Adrenocortical Carcinoma: the Posterior Minimally Invasive Approach -- 12. Surgery for Malignant Pheochromocytoma -- 13. Open or Laparoscopic Surgery in the Management of Adrenocortical Carcinoma? -- 14. Pathology of Adrenocortical Carcinoma and Malignant Pheochromocytoma -- 15. Medical Treatment in Advanced Adrenocortical Carcinoma -- 16. Integrated Approach in Locally Advanced, Oligometastatic or Recurrent Adrenocortical Carcinoma -- 17. Medical Treatment of Malignant Pheochromocytoma -- 18. Role of Radiotherapy in Adrenocortical Carcinoma and Pheochromocytoma -- 19. Radionuclide Treatment in Malignant Pheochromocytoma -- 20. Preclinic and Translational Research in Adrenal Malignancies.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Surgery; Internal medicine; Genetics; Radiology; Oncology; Medicine -- Research; Biology -- Research; General Surgery; Internal Medicine; Genetics; Radiology; Oncology; Translational Research